Insights into the impact of manure on the environmental antibiotic residues and resistance pool - Marutescu, Luminita Gabriela; Jaga, Mihaela; Postolache, Carmen; Barbuceanu, Florica; Milita, Nicoleta Manuela; Romascu, Luminita Maria; Schmitt, Heike; de Roda Husman, Ana Maria; Sefeedpari, Paria; Glaeser, Stefanie; Kämpfer, Peter; Boerlin, Patrick; et al. (Frontiers in Microbiology, 2022)
The intensive use of antibiotics in the veterinary sector, linked to the application of manure-derived amendments in agriculture, translates into increased environmental levels of chemical residues, AR bacteria (ARB) and antibiotic resistance genes (ARG). This review aims to evaluate the current evidence regarding the impact of animal farming and manure application on the antibiotic resistance pool in the environment. The soils fertilized with manure-derived products harbor a higher and chronic abundance of ARB, multiple ARG and an enriched associated mobilome, which is also seen in crops grown on amended soils. Different manure processing techniques have various efficiencies in the removal of antibiotic residues, ARB and ARGs, but there is only a small amount of data from commercial farms. The efficiency of sludge anaerobic digestion appears to be dependent on the microbial communities composition, the ARB/ARG and operating temperature (mesophilic vs. thermophilic conditions). Composting seems to reduce or eliminate most of antibiotics residues, enteric bacteria, ARB and different representative ARG in manure more rapidly and effectively than lagoon storage. Our review highlights that despite the body of research accumulated in the last years, there are still important knowledge gaps regarding the contribution of manure to the AMR emergence, accumulation, spread and risk of human exposure in countries with high clinical resistance rates. Land microbiome before and after manure application, efficiency of different manure treatment techniques in decreasing the AMR levels in the natural environments and along the food chain must be investigated in depth, covering different geographical regions and countries and using harmonized methodologies. The support of stakeholders is required for the development of specific best practices for prudent – cautious use of antibiotics on farm animals. The use of human reserve antibiotics in veterinary medicine and of unprescribed animal antimicrobials should be stopped and the use of antibiotics on farms must be limited. This integrated approach is needed to determine the optimal conditions for the removal of antibiotic residues, ARB and ARG, to formulate specific recommendations for livestock manure treatment, storage and handling procedures and to translate them into practical on-farm management decisions, to ultimately prevent exposure of human population.